Book reviews: Gurgu Elena – The globalization of the economic activity. Relations and tendencies - MECU, Constantin (Annals of Spiru Haret University. Economic Series, 2011)
As we know, the economic globalisation, correlated to other similar processes, changes the world’s configuration, if that hasn’t happened yet. People worldwide seem to increasingly realize that they belong to the world itself and not to small communities, that their development does not depend on the development of the communities, but on decision-making processes they never knew existed. In this respect, I mention a relevant case. The thousands of Romanian female textile workers active in lohn manufacturing for many years lost their jobs on account of such unknown forces. In fact, these processes emerge following production globalisation.